Deficiencies in the administration and execution of the budget in Educational Services Funds (2019)
The Educational Services Funds (ESF) emerged as accounting accounts created as a budgetary and resource management mechanism according to Law 715 of 2001, and with these seeks to create adequate spaces for the development of academic activities and the institutional horizon. These funds are administered by a Rector Managing Director, who is called the "expenditure computer" and is in charge of directing the resources and complying with all the budget execution parameters established in the standard. By analyzing the budgetary execution of the ESFs belonging to the municipality of Funza, we will analyze whether the managing directors are fulfilling this task, and whether the requirements demanded of them for the development of this function are in accordance with this administrative management.